A longitudinal study of lameness incidence and association with animal-based welfare measures in dairy cows - Sadiq, Mohammed Babatunde; Ramanoon, Siti Zubaidah; Shaik Mossadeq, Wan Mastura; Mansor, Rozaihan; Syed Hussain, Sharifah Salmah (Universiti Putra Malaysia Press, 2021)
The objective of this study was to investigate time to lameness event, prevalence of claw lesions, and their associations with animal-based welfare measures (ABWMs) in dairy cows. A total of 120 non-lame lactating cows (n = 30 each from four intensive dairy farms) having no claw lesion were enrolled in the study. The cow-level enrollment criteria included good body condition score (BCS), normal hock condition score, absence of body injuries, and normal claw length. Information on cows’ parity, milk yield, and previous lameness event (PLE) were recorded. The cows were observed twice monthly (every 2 weeks) for locomotion scores (LS), and ABWMs, whereas claw lesions were recorded upon onset of lameness and at the end of the observation period. Cows were considered lame when 2 consecutive LS = 3, or any assessment with score 4. Cox regression models were used to investigate lameness incidence and the association with ABWMs, while association between the latter and claw horn lesions (CHL) prevalence were analyzed using logistic regression models. Twenty-four percent (29/120) of the cows were lame during the study period. Lameness risk was associated with PLE (Hazard ratio; HR = 7.4; 95% CI 2.4-23.0), presence of overgrown claw (HR = 3.7; 95% CI 1.1-12.6) and low BCS pre-lame (HR = 4.5; 95% CI 1.3-16.6). Amongst the cows affected with claw lesions, 68.4% (37/44) were lame and CHL were predominant (75.4%) compared to infectious claw lesions (24.7%). Cows with lower BCS (< 3.0) (OR = 5.7; 95% CI 1.6- 20.4) and those with PLE (OR = 7.2; 95% CI = 2.1-24.7) were more likely to have CHL. Management practices such as maintaining cows’ body condition, improved care for those with history of lameness, and proper claw trimming could assist farmers to reduce lameness incidence in the studied herds.